Variables associated with sleep quality in chronic tension-type headache: A cross-sectional and longitudinal design - Benito-González, Elena; Palacios-Ceña, Maria; Fernández-Muñoz, Juan J.; Castaldo, Matteo; Wang, Kelun; Catena, Antonella; Arendt-Nielsen, Lars; Fernández-de-las-Peñas, César (PLOS ONE, 2018)
Objective To investigate variables associated at baseline (cross-sectional design) and at one year (longitudinal design) with the quality of sleep in chronic tension-type headache (CTTH). Methods One hundred and eighty (n = 180) and 135 individuals with CTTH participated in the cross-sectional and longitudinal design respectively. Clinical features were collected with a 4-weeks headache diary at baseline and one-year follow-up. Sleep quality was assessed at baseline and 1-year follow-up with the Pittsburgh Sleep Quality Index. Anxiety and depression (Hospital Anxiety and Depression Scale-HADS), burden of headache (Headache Disability Inventory-HDI), quality of life (SF-36 questionnaire), and pressure pain thresholds (PPTs) at trigeminal, extra-trigeminal and widespread area were assessed at baseline. Hierarchical regression analyses were conducted to determine the associations between variables at baseline and 1-year follow-up with sleep quality. Results At baseline positive correlations between sleep quality and headache intensity, headache frequency, headache duration, emotional and physical burden of headache and depression were observed. The regression analyses found that depression and emotional burden of headache explained 27.5% of the variance in sleep quality at baseline (r2 = .262; F = 23.72 P < .001). At one-year, sleep quality was significantly associated with baseline burden of headache, depression, widespread PPTs, vitality and mental health domains. Regression analyses revealed that vitality, PPT over the second metacarpal and PPT over the neck explained 30.0% of the variance of sleep quality at one-year (r2 = .269, F = 9.71, P < .001). Conclusions It seems that sleep quality exhibits a complex interaction in individuals with CTTH since depression and the emotional burden were associated with sleep quality at baseline, but vitality and PPTs over extra-trigeminal areas were associated with the quality of sleep at one-year.